Analisis keterampilan sosial peserta didik dalam pembelajaran IPS kelas V sekolah dasar - Alfina Nur Rizky; Siti Istiyati; Siti Kamsiyati (Didaktika Dwija Indria, 2022)
This study aims to describe the social skills of students in social studies learning inclass V SD N Sondakan No. 11 Surkarta for the 2021/2022 academic year. This research is classified into qualitative descriptive research. The research was carried out in May-June 2022 which took place at SD N Sondakan No. 11 Surakarta. The subjects of this study were students of class V. Data collection techniques were through observation, questionnaire assessment, interviews, and documentation. Analysis of the data used is the analytical technique of Miles & Huberman through data collection, data reduction, data presentation, and drawing conclusions. The validity of the data using triangulation techniques and sources. The results of the study showed that the average results of observations and questionnaires from 6 students were 72.70%. The average result of the highest aspect of social skills is the aspect of relationships with peers of 80.72%. The average result of the lowest aspect of social skills is the aspect of self-assertion of 60.93%. Overall, the research results can be concluded that students who are included in the good category of social skills students have appropriate, suitable, and not much different observations, questionnaires, and interviews scores, as well as students with fairly good and poor categories.